Alkaline Water Oxidation Using a Bimetallic Phospho‐Boride Electrocatalyst. Issue 24 (11th November 2020) - Chunduri, Avani; Gupta, Suraj; Patel, Maulik; Forster, Mark; Cowan, Alexander J.; Patel, Nainesh
Abstract: New oxygen evolution reaction (OER) electrocatalysts based on low‐cost elements, which set new benchmark levels of activity, are vital if water electrolysis is to be applied on a global scale. Herein, a low‐cost bimetallic phospho‐boride catalyst was developed that showed outstanding OER activity of approximately 195 mV to achieve 10 mA cm −2 in alkaline water electrolysis, with a minimal catalyst loading of 0.3 mg cm −2 . The contrasting electron transfer property of the metal borides and phosphides when combined in phospho‐boride modulated the electron density of the Co atom, yielding highly active CoOOH species at lower potentials. The addition of Mo at low levels further enhanced the activity by increasing the surface area and by formation of nano‐crystalline domains. The combined contributions from each of the components resulted in a new benchmark mass activity of 666 A g −1 at 300 mV overpotential. This work presents a new avenue towards fabricating electrode materials with exceptional performances. Abstract : Twice the fun : The electrocatalytic performance of a novel bimetallic phospho‐boride catalyst for oxygen evolution reaction in alkali electrolyte is investigated. The unique configuration offers electron modulation of active Co sites and an enhanced surface area to achieve a new benchmark mass activity with a minimal catalyst loading, making it one of the most active oxygen evolution reaction catalysts to date.